2010
DOI: 10.1353/lag.2010.0024
|View full text |Cite
|
Sign up to set email alerts
|

Community Expansion and Infrastructure Development: Implications for Human Health and Environmental Quality in the Galápagos Islands of Ecuador

Abstract: Este estudio investiga la comunidad de Puerto Villamil ubicada en la Isla Isabela del archipiélago de los Galápagos. Se examina el desarrollo urbano y las interacciones humanas-ambientales a través de una perspectiva de la ciencia de información geográfica que incluye: (1) la construcción de una serie de tiempo de fotografías aéreas e imagenes satélites, (2) el mapeo de la infraestructura de agua y alcantarillado actual dentro el contexto del crecimiento comunal, con especial referencia a las medidas de la cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The findings of this study agree with the conclusion of Walsh et al (2010) that population growth on the Galápagos may be threatening not only the natural environment, but potentially public health on the Islands. This study is the first to examine the presence of antibiotic resistance in sewage and recreational water on the Galápagos Islands.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of this study agree with the conclusion of Walsh et al (2010) that population growth on the Galápagos may be threatening not only the natural environment, but potentially public health on the Islands. This study is the first to examine the presence of antibiotic resistance in sewage and recreational water on the Galápagos Islands.…”
Section: Discussionsupporting
confidence: 91%
“…Sewage treatment systems on the islands are either not present, or are frequently dysfunctional or not in operation. This wastewater may pose a potential public health risk and may threaten the habitats which comprise the unique ecosystem that sustains the growing economy (Epler, 2007;Watkins and Cruz, 2007;Walsh et al, 2010). The Galápagos Islands have a residential population of about 30,000 and almost 200,000 tourists visit the islands each year (Epler, 2007;Galapagos National Park Service, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Issues of land-use change, lack of services, insufficient public transport facilities, and alien species introductions, among others, are typical of human settlements, and Galápagos is no exception. In Puerto Villamil on Isabela Island, Walsh et al (2010) demonstrated how lack of adequate design and engineering in urban and rural planning has had implications for the health of residents as well as for the fauna and flora of the archipelago.…”
Section: Developmentmentioning
confidence: 99%